Participation of Zimbabwean youths in electoral processes: a case of Harare Central Constituency 2008 to 2013 - Chikowore, Vimbayi (Midlands State University, 2017)
Contemporary global trends show a growing international anxiety for youth empowerment. Since independence Zimbabwe has incessantly experienced a decline in youth electoral participation. In Zimbabwe, youths represent 67 % of the country’s population; according to the new constitution youth fall in between the ages of 16 and 35 years. Compared to older citizens, youth especially females have increasingly preferred to stay away from participating in electoral processes and their participation from legal framework crafting to the pre electoral period, the actual electoral period and the post electoral period has been considerably low. The period between the years 2008 to 2013 brought its own challenges ranging from economic, social and political factors which have negative impact on youth participation in electoral processes. The participation of youth in electoral processes has become a major concern in the political development of many countries in the developing world. Participation of youth is declining fast and much needs to be done to ensure youth participation in the electoral processes. Be that as it may, this study seeks to examine the participation of youth in electoral processes in a bid help come up with solutions to this problem.